(untitled) (Pedagogical Horizons, 2020)
The focus of this article is on the possibilities that work with lyrical texts in the context of linguistic education in primary school offers for dealing with questions of identity and belonging in a school characterized by multilingualism and migration, diversity and heterogeneity. According to numerous studies, the implementation of a language-promoting learning environment, the successful promotion and development of (critical) language use, and also a discussion of individual and social multilingualism - also with regard to questions of belonging and participation in the sense of an inclusive school – depends on the competence of the teachers. According to empirical teaching research, these competencies for professionalized, inclusive teaching practice are highly dependent on attitudes and attitudes - the teacher’s beliefs. Teacher Beliefs are seen as an influential variable in the design of lessons. Especially with regard to heterogeneity as a defining characteristic of everyday school life, these play an important role, since they are a value-based, individual, clusters-based system of convictions, which partly controls consciously, partly unconsciously, one’s own actions. But how can this value system be accessed and how can it be influenced? Answers can be found in the model of “Emergent Learning” according to Taylor, which is outlined in this article and associated with heterogeneity and poetry in the context of teaching in inclusive-sensitive schools. Based on the assumption that teachers can see themselves in their role as teachers and also as learners, and if they can engage with the pupils in personality-developing, emergent learning processes, the contribution should address the question of what possibilities of influencing the work with lyrical texts in primary school can be attributed to dealing with heterogeneity.